PERANAN PENDIDIKAN PANCASILA DALAM MEMBENTUK KARAKTER BANGSA - Febrianti, Eka; Viani, Theresia Patria; Priscilia, Lidwina; Senjani, Dita Permata; Ghaisani, Kayla Rossita; Tumanggor, Raja Oloan (Cahaya Ilmu Bangsa Institute, 2024)
Pancasila has an important role in forming the basis of social and state life in Indonesia and is the main foundation for all citizens in life in Indonesia. As a way of life, Pancasila also has an important role in shaping the character and personality of the Indonesian people. Every Indonesian citizen is obliged to understand and apply all the values contained in Pancasila. Through Pancasila Education, it is hoped that educational institutions can become a forum for applying the values contained in Pancasila. Both in the educational environment and social life, educational institutions must play an active role in instilling and practicing these values. In addition, as a citizen, it is important to have the character of state defense, namely the attitudes and actions of citizens based on a sense of love for the country, awareness of nation and state, belief in Pancasila as the state ideology. State defense has the aim of improving welfare, educating the life of the nation and state, carrying out order based on peace and social justice which are the functions and goals of the nation. Of course, in this case Pancasila plays an important role in shaping a new generation with a national outlook and character by applying the attitude of state defense and incorporating moral values into everyday life so that by applying Pancasila education is very important and there is no doubt because it teaches individuals the value of applying Pancasila principles in social interactions and equips individuals with virtues to face global challenges as good citizens. Pancasila memiliki peran penting dalam membentuk dasar kehidupan bermasyarakat serta bernegara di Indonesia dan menjadi landasan utama bagi seluruh warga negara dalam kehidupan di Indonesia. Sebagai pedoman hidup, Pancasila juga memiliki peran penting dalam membentuk karakter serta kepribadian bangsa Indonesia. Setiap warga negara Indonesia berkewajiban untuk memahami serta menerapkan seluruh nilai yang terkandung dalam Pancasila. Melalui Pendidikan Pancasila, diharapkan lembaga pendidikan dapat menjadi wadah dalam menerapkan nilai-nilai yang terkandung dalam Pancasila. Baik dalam lingkungan pendidikan maupun kehidupan sosial, lembaga pendidikan harus berperan aktif dalam menanamkan dan mengamalkan nilai-nilai tersebut. Selain itu sebagai warga negara, penting memiliki karakter bela negara yaitu sikap dan tindakan warga negara yang didasari oleh rasa cinta tanah air, kesadaran berbangsa dan bernegara, keyakinan pada Pancasila sebagai ideologi negara. Bela negara memiliki tujuan untuk meningkatkan kesejahteraan, mencerdaskan kehidupan bangsa dan negara, menjalankan ketertiban berdasarkan pada perdamaian serta keadilan sosial yang merupakan fungsi dan tujuan bangsa. Tentunya dalam hal ini Pancasila memainkan peran penting dalam membentuk generasi baru yang berwawasan kebangsaan dan berkarakter dengan menerapkan sikap bela negara serta memasukkan nilai-nilai moral ke dalam kehidupan sehari-hari sehingga dengan menerapkan pendidikan Pancasila sangat penting dan tidak perlu diragukan lagi karena mengajarkan individu pada nilai penerapan prinsip-prinsip Pancasila dalam interaksi sosial dan membekali individu dengan kebajikan untuk menghadapi tantangan global sebagai warga negara yang baik.